Implementation of Green Accounting to Support the Sustainability of Our Tempe Kita MSMES in Kotapinang, South Labuhanbatu Regency - Nasution, Mei Lani; Daulay, Aqwa Naser; Harmain, Hendra (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2025)
This study aimed to analyze the implementation of green accounting in the traditional food sector MSME â€œTempe Kitaâ€ in Kotapinang, South Labuhanbatu Regency, and its contribution to business sustainability. The research used a case study method with a qualitative approach through observation, in-depth interviews, and documentation. The results showed that the MSME had applied sustainability principles, particularly in waste management and resource efficiency, although these efforts had not been systematically documented. The adoption of green accounting principles remained limited, with no recognition of environmental assets and liabilities or integrated reporting. The MSME had allocated some environmental costs but had not yet covered all necessary cost categories. In general, the implementation of green accounting was still simple but demonstrated an initial commitment to sustainable practices. The study recommended the need for training, technical assistance, and the development of an environmental recording system suited to the capacity of MSME to enhance their contribution to sustainable development.